Mediating Effect of Cultural Intelligence on Personality Traits and Intercultural Effectiveness Among Senior High School Students - Salas, Jessilda A.; Hermosa, Jherwin P. (International Journal of Multidisciplinary: Applied Business and Education Research, 2025)
is study examined the mediating role of Cultural Intelligence (CQ) in the relationship between personality traits and intercultural effective-ness among Senior High School students. In an increasingly globalized world, developing intercultural competence is essential for students to navigate diverse cultural environments effectively.The study employed a quantitative approach, gathering infor-mation from 100 Senior High School students in San Vicente Integrat-ed High School through a survey method. The Big Five Personality Traits questionnaire, the Cultural Intelligence Scale, and the Intercul-tural Effectiveness Scale were among the tools used in the survey.Mean and Standard Deviation were used to describe the responses of the respondents in their perceptions of Personality Traits, Intercul-tural Effectiveness, and Cultural Intelligence. Also, the Pearson prod-uct-moment correlation coefficient was used to determine the rela-tionship between Personality Traits and Intercultural Effectiveness. PROCESS Macro was used in Mediation Analyses.The findings show a positive correlation between higher levels of intercultural effectiveness and specific personality traits, namely con-scientiousness and openness to new experiences. Moreover, cultural intelligence significantly mediates this relationship, showing that stu-dents with higher Cultural Intelligence (CQ) are better able to leverage their personality traits to enhance their intercultural effectiveness.The results show how crucial it is to develop cultural intelligence in learning environments to get students ready for cross-cultural interac-tions. The development of focused interventions and instructional strategies that raise students' CQ and improve their capacity to per-form well in a variety of cultural contexts are examples of practical results.